Parotid sialolithiasis and sialadenitis in a 3-year-old child: a case report and review of the literature - Nur Eliana Ahmad Tarmizi; Suhana Abdul Rahim; Avatar Singh Mohan Singh; Lina Ling Chooi; Fei Ming Ong; Sai Guan Lum (SpringerOpen, 2020)
Abstract Background Salivary gland calculi are common in adults but rare in the paediatric population. It accounts for only 3% of all cases of sialolithiasis. Parotid ductal calculus is rare as compared to submandibular ductal calculus. Case presentation A 3-year-old boy presented with acute painful right parotid swelling with pus discharge from the Stensen duct. Computed tomography revealed calculus obstructing the parotid duct causing proximal ductal dilatation and parotid gland and masseter muscle oedema. The child was treated with conservative measures, and subsequently the swelling and calculus resolved. Conclusions Small parotid duct calculus in children may be successfully treated with conservative measures which obviate the need for surgery. We discuss the management of parotid sialolithiasis in children and conduct literature search on the similar topic.